Inheritance of effective juvenile leaf rust resistance in six accessions of Aegilops speltoides Tausch - M. A. Kolesova; L. G. Tyryshkin (Труды по прикладной ботанике, генетике и селекции)
Background. Leaf rust (causal agent: Puccinia triticina Erikss.) is a serious disease of bread wheat in all crop-growing regions. An environmentally safe and economically profitable method to protect plants is cultivation of resistant varieties. Their development requires searching for the forms carrying new genes of resistance. Despite the fact that more than 70 Lr genes have been described, only two (Lr39(41) and Lr47) are effective in the seedling stage over all the territory of the Russian Federation. Thus, expanding the set of effective leaf rust resistance genes is a high-priority task. An important source of such genes are wild relatives of Triticum aestivum L., including Aegilops L. species. Knowing genetic control of resistance in newly identified forms will help to avoid the transfer of the same alien resistance genes onto bread wheat. Materials and methods. Inheritance of effective juvenile leaf rust resistance was studied in 6 accessions of Ae. speltoides Tausch from the VIR collection. Crossings were carried out in the field of Pushkin and Pavlovsk Laboratories of VIR (St. Petersburg). Genetic control of resistance to the disease was analyzed in the following accessions of Ae. speltoides: k-1000 (Turkey), k-1015 (Afghanistan), k-1593 (Iraq), k-2279 (Iran), k-2753 and k-2819 (unknown origin). Results and conclusions. The analysis of segregation for seedling resistance to leaf rust in F2 и F3 from the crosses between the 6 studied accessions and the susceptible Ae. speltoides accession k-1596 showed that each of them possessed one dominant resistance gene. The absence of susceptible plants in hybrid populations from the crosses between resistant accessions testified to a tight linkage or, more likely, the identity of their genes associated with resistance. The identified resistance gene cannot be identical to Lr28, Lr35, Lr36 and Lr51, earlier introgressed into the T. aestivum genome from Ae. speltoides. Before the introgression of the newly identified gene, it is necessary to study its identity to Lr47 using the phytopathological test; the use of molecular markers for this purpose is little informative.